Erratum to: Ockham’s razor for the MET-driven invasive growth linking idiopathic pulmonary fibrosis and cancer - Giulia M. Stella; Alessandra Gentile; Alice Balderacchi; Federica Meloni; Melissa Milan; Silvia Benvenuti (Journal of Translational Medicine, 2017)
Abstract In the original version of this article [1], published on 2 September 2016, the name of author ‘Alice Balderacchi’ was wrongly displayed. In this Erratum the incorrect name and correct name are shown. The original publication of this article has been corrected.